An integrated community‐based outpatient therapeutic feeding programme for severe acute malnutrition in rural Southern Ethiopia: Recovery, fatality, and nutritional status after discharge - Tadesse, Elazar (Matern Child Nutr, 2017)
A scaled up and integrated outpatient therapeutic feeding programme (OTP) brings the treatment of severely malnourished children closer to the community. This study assessed recovery from severe acute malnutrition (SAM), fatality, and acute malnutrition up to 14 weeks after admission to a programme integrated in the primary health care system. In this cohort study, 1,048 children admitted to 94 OTPs in Southern Ethiopia were followed for 14 weeks. Independent anthropometric measurements and information on treatment outcome were collected at four home visits. Only 32.7% (248/759) of children with SAM on admission fulfilled the programme recovery criteria at the time of discharge (i.e., gained 15% in weight, or oedema, if present at admission, was resolved at discharge). Of all children admitted to the programme for whom nutritional assessment was done 14 weeks later, 34.6% (321/928) were severely malnourished, and 37.5% (348/928) were moderately malnourished; thus, 72.1% were acutely malnourished. Of the children, 27/982 (2.7%) had died by 14 weeks, of whom all but one had SAM on admission. Children with severe oedema on admission had the highest fatality rate (12.0%, 9/75). The median length of admission to the programme was 6.6 weeks (interquartile range: 5.3, 8.4 weeks). Despite children participating for the recommended duration of the programme, many children with SAM were discharged still acutely malnourished and without reaching programme criteria for recovery. For better outcome of OTP, constraints in service provision by the health system as well as challenges of service utilization by the beneficiaries should be identified and addressed.